Effects of Lactobacillus plantarum fermented Shenling Baizhu San on gut microbiota, antioxidant capacity, and intestinal barrier function of yellow-plumed broilers - Lv, Weijie; Ma, Yimu; Zhang, Yingwen; Wang, Tianze; Huang, Jieyi; He, Shiqi; Du, Hongliang; Guo, Shining (Frontiers in Veterinary Science, 2023)
The current study focused on the effects of Shenling Baizhu San (SLBZS) fermented by Lactobacillus plantarum (L. plantarum) on gut microbiota, antioxidant capacity, and intestinal barrier function of yellow-plumed broilers. Our results showed that the content of ginsenoside Rb1 was the highest when SLBZS were inoculated with 3% L. plantarum and fermented at 28°C for 24 h. One-day-old male broilers were divided into five treatment groups. Treatment consisted of a basal diet as a control (Con), 0.1% unfermented SLBZS (U-SLBZS), 0.05% fermented SLBZS (F-SLBZS-L), 0.1% fermented SLBZS (F-SLBZS-M), and 0.2% fermented SLBZS (F-SLBZS-H). On days 14, 28, and 42, six chickens from each group were randomly selected for blood collection and tissue sampling. The results showed that the addition of 0.1% fermented SLBZS could significantly increase average daily feed intake (ADFI) and average daily gain (ADG), and decrease feed conversion ratio (FCR) of broilers. The addition of 0.1 and 0.2% fermented SLBZS significantly increased the lymphoid organ index of broilers on day 28 and 42. The addition of 0.1 and 0.2% fermented SLBZS could improve the antioxidant capacity of broilers. Moreover, the addition of 0.1 and 0.2% fermented SLBZS could significantly increase the villus height/crypt depth of the ileum, and significantly increase the expression of tight junction. In addition, fermentation of SLBZS increase the abundance of Coprococcus, Bifidobacterium and Bilophila in the gut of broilers. These results indicate that the supplementation of fermented SLBZS in the diet could improve the growth performance, lymphoid organ index, antioxidant capacity, and positively affect the intestinal health of broilers.